The Authority of Texts in the Dynamics of Ijtihad on Fiqh Mu'amalah Among Santri in Indonesia - Mustofa, Imam; Setiawan, Wahyu; Maliki, Ibnu Akbar; Chamdan, Umar (El-Mashlahah, 2024)
Text is one of the most important elements for Muslims. It not only acts as a symbol but also a representation of authority that connects family identity among Muslim communities. In the world of pesantren (Islamic boarding schools), ijtihad is one means of reproducing text authority, including in the fiqh mu’amalah. The article aimed to examine the authority of the text in the ijtihad of the fiqh mu’amalah of Islamic boarding schools in Indonesia. The article is the result of normative legal research with a qualitative descriptive research design. Meanwhile, the research objects studied and examined were related to text and authoritative power in the ijtihad of santri (Islamic students) in pesantren (Islamic boarding schools). The study showed that as authoritative power, santri plays a role in transferring the text of the kitab kuning (yellow book) in the discourse of fiqh mu’amalah, both explicitly (qawli) and implicitly (ilhaqi), as legitimacy for the decisions made in the bahsul masail forum. Based on the concept of El-Fadl’s authority, the role of santri as the authoritative power of the text in ijtihad is based on five foundations, honesty and openness, sincerity in understanding "God’s will" in the text, the principle of comprehensiveness, rationalization of interpretation and search for "God’s command," and the ability to self-control in ijtihad. This study recommends that the bahsul masail methodology be preserved, either in the pesantren environment or formal education, affiliated with the pesantren. So, the religious texts are interpreted and read properly according to their context.